The Repatriation of Foreign Terrorist Fighters in Indonesia: Its Dilemma and Debates - Siti Rachma; Muhammad A.S. Hikam; Fahlesa Munabari (Universitas Budi Luhur, 2022)
ISIS (Islamic State in Iraq and Syria) has expanded its movement to Southeast Asia, including Indonesia which once got attacked by terrorist as the country becomes terrorists’ preferred place to travel and execute their plans in conflict zones. To tackle this problem, Indonesian government had issued a policy to avoid negative implications upon the return of Indonesian nationals linked to terrorism from abroad (Foreign Terrorist Fighters or FTF). The government was considering whether or not to repatriate FTF since this plan remains a debatable issue in Indonesia. The government was concerned with the possibility of them recruiting new members. On the other side, humanity becomes the opposite reason leading to the acceptance of the extremist repatriation policy. Due to the urgency of the rampant terrorist threats and the consequences, the Indonesian government has decided to implement the repatriation policy. The government ended up refusing the repatriation of Indonesian nationals linked to terrorism abroad to protect the national security. This article elaborates the radicalization mechanism, terrorist recruitment process based on the national security theory. This study also explains the urgent situation and condition that made the government apply refusal against repatriation. There are still considerable challenges regarding the repatriation policy that need to be addressed such as relevant infrastructure and effective regulations.